1992
DOI: 10.1111/j.1748-1716.1992.tb09423.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms in man for rapid refill of the circulatory system in hypovolaemia

Abstract: Compensatory, net fluid transfer across the capillaries was studied in the arm of man with plethysmographic technique during experimental hypovolaemia induced by lower body negative pressure (LBNP). Thirty, 60, and 110 cmH2O LBNP evoked rapid transfer of fluid from tissue to blood at average rates of 0.053, 0.088 and 0.147 ml min-1 100 ml-1 soft tissue, i.e. graded responses typical for a true homeostatic regulation. Other experiments demonstrated a net fluid absorption not only from the arm but also from a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…*Sex differences (P Ͻ 0.05). which it was initiated seems to be of importance for the cardiovascular response, since a more rapidly induced hypovolemic stimulus elicits a greater circulatory response (28). No sex differences in Cap 50 were found, however.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…*Sex differences (P Ͻ 0.05). which it was initiated seems to be of importance for the cardiovascular response, since a more rapidly induced hypovolemic stimulus elicits a greater circulatory response (28). No sex differences in Cap 50 were found, however.…”
Section: Discussionmentioning
confidence: 88%
“…The combined effect of the capacitance response and transcapillary fluid absorption during the limited period of 8 min of hypovolemic circulatory stress, corresponding to LBNP of 44 mmHg, adds another 900 ml to the effective circulating blood volume. A well-maintained capacitance response and net capillary fluid absorption seem to constitute very important compensatory responses for the restitution of plasma volume during acute hemorrhage and hypovolemia (28). The inability for women compared with men to defend central blood volume with time might thus be due to the reduced capacitance response with time and decreased net capillary absorption, leading to a decrease in venous return to the heart and thus a more prominent reduction in stroke volume.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies in healthy subjects without a history of VVS have suggested that not just the pooled volume, but also the rate by which the hypovolemic stimulus is instituted can affect the responses to orthostatic stress (27,77). Despite a similar capacitance response, Lindenberger and Länne (77) found a much slower lower limb blood pooling in otherwise healthy women experiencing vasovagal reactions during moderate levels of LBNP compared to hemodynamic stable women.…”
Section: Pathophysiology Of Vasovagal Syncopementioning
confidence: 99%
“…Fluid absorption from tissue to blood serves as a powerful mechanism to increase plasma volume during hypovolemic stress (27)(28)(29)(30) and an effective fluid absorption is dependent on both a high hydrodynamic conductivity (i.e., CFC), and a reflex decline in capillary pressure due to α-and β-adrenergic adjustment of pre-and postcapillary resistance (25,26). The present finding of a similar calf CFC between VVS and controls makes capillary fluid permeability characteristics unlikely as an explanation of the differences in net fluid absorption.…”
Section: Mobilization Of Venous Blood and Fluid Absorptionmentioning
confidence: 99%
See 1 more Smart Citation